Biogeochemical controls on dissolved micronutrient (Ni, Cu, Zn, Cd) distributions in the Equatorial Pacific Ocean - Naman D. Singh; Zvi Steiner; Rena Czeschel; Peter Brandt; Yuping Guo; Xue-Gang Chen; Jana Blanke; Angèle Nicolas; Jinqiang Guo; Kathleen J. Gosnell; Edel M. O’Sullivan; Dominik Jasinski; et al. (Geochimica et Cosmochimica Acta, 2026)

The Citizen Science Stream Index - a simple and effective citizen science biomonitoring protocol using six key macroinvertebrate indicator taxa - Simon Harrison; Brendan McSorley; Tim Sullivan (Science of The Total Environment, 2025)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Elevated CO2 and phosphorus deficiency interactively enhance root exudation in Lupinus albus L. - James B. O’Sullivan; Tim Plozza; Dario Stefanelli; Jian Jin; Caixian Tang (Plant and Soil, 2021)

Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Emily Ogier; Sarah Jennings; Anthony Fowler; Stewart Frusher; Caleb Gardner; Paul Hamer; Alistair J. Hobday; Adrian Linanne; Stephan Mayfield; Craig Mundy; Andrew Sullivan; Geoff Tuck; et al. (Frontiers in Marine Science, 2020)

Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Jörn O. Schmidt; Steven J. Bograd; Haritz Arrizabalaga; José L. Azevedo; Steven J. Barbeaux; John A. Barth; Tim Boyer; Stephanie Brodie; Juan José Cárdenas; Scott Cross; Jean-Noël Druon; Agneta Fransson; et al. (Frontiers in Marine Science, 2019)

Species Matter: Wood Density Influences Tropical Forest Biomass at Multiple Scales - Oliver L. Phillips; Martin J. P. Sullivan; Tim R. Baker; Abel Monteagudo Mendoza; Percy Núñez Vargas; Rodolfo Vásquez (Surveys in Geophysics, 2019)

Risk-based approach to developing a national residue sampling plan for testing under European Union regulation for veterinary medicinal products and coccidiostat feed additives in domestic animal production - Martin Danaher; Conor Shanahan; Francis Butler; Rhodri Evans; Dan O’Sullivan; Denise Glynn; Tim Camon; Peadar Lawlor; Michael O’Keeffe (Food Additives & Contaminants: Part A, 2016)

Corrigendum to Cameron et al . 2013 - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)

Eco‐evolutionary dynamics in response to selection on life‐history - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)
Understanding the consequences of environmental change on ecological and evolutionary dynamics is inherently problematic because of the complex interplay between them. Using invertebrates in microcosms, we characterise phenotypic, population and evolutionary dynamics before, during and after exposure to a novel environment and harvesting over 20 generations. We demonstrate an evolved change in life‐history traits (the age‐ and size‐at‐maturity, and survival to maturity) in response to selection caused by environmental change (wild to laboratory) and to harvesting (juvenile or adult). Life‐history evolution, which drives changes in population growth rate and thus population dynamics, includes an increase in age‐to‐maturity of 76% (from 12.5 to 22 days) in the unharvested populations as they adapt to the new environment. Evolutionary responses to harvesting are outweighed by the response to environmental change (~ 1.4 vs. 4% change in age‐at‐maturity per generation). The adaptive response to environmental change converts a negative population growth trajectory into a positive one: an example of evolutionary rescue.

Development and Characterization of Genomic and Gene-Based Microsatellite Markers in North American Red Oak Species - Alexis R. Sullivan; Jennifer F. Lind; Tim S. McCleary; Jeanne Romero-Severson; Oliver Gailing (Plant Molecular Biology Reporter, 2013)

Phenotypic assessment of galanin overexpressing and galanin receptor R1 knockout mice in the tail suspension test for depression-related behavior - Andrew Holmes; Qian Li; Elizabeth A. Koenig; Eric Gold; Dejaimenay Stephenson; Rebecca J. Yang; Jennifer Dreiling; Tim Sullivan; Jacqueline N. Crawley (Psychopharmacology, 2005)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)